The Way of Medicine : Ethics and the Healing Profession - Curlin, Farr A.; Tollefsen, Christopher (Book collections on Project MUSE., 2021)
Today's medicine is spiritually deflated and morally adrift; this book explains why and offers an ethical framework to renew and guide practitioners in fulfilling their profession to heal. What is medicine and what is it for? What does it mean to be a good doctor? Answers to these questions are essential both to the practice of medicine and to understanding the moral norms that shape that practice. The Way of Medicine articulates and defends an account of medicine and medical ethics meant to challenge the reigning provider of services model, in which clinicians eschew any claim to know what is good for a patient and instead offer an array of "health care services" for the sake of the patient's subjective well-being. Against this trend, Farr Curlin and Christopher Tollefsen call for practitioners to recover what they call the Way of Medicine, which offers physicians both a path out of the provider of services model and also the moral resources necessary to resist the various political, institutional, and cultural forces that constantly push practitioners and patients into thinking of their relationship in terms of economic exchange. Curlin and Tollefsen offer an accessible account of the ancient ethical tradition from which contemporary medicine and bioethics has departed. Their investigation, drawing on the scholarship of Leon Kass, Alasdair MacIntyre, and John Finnis, leads them to explore the nature of medicine as a practice, health as the end of medicine, the doctor-patient relationship, the rule of double effect in medical practice, and a number of clinical ethical issues from the beginning of life to its end. In the final chapter, the authors take up debates about conscience in medicine, arguing that rather than pretending to not know what is good for patients, physicians should contend conscientiously for the patient's health and, in so doing, contend conscientiously for good medicine. The Way of Medicine is an intellectually serious yet accessible exploration of medical practice written for medical students, health care professionals, and students and scholars of bioethics and medical ethics.